Assessment of Microplastic Contamination in Coastal Waters of Southeast Asia: Implications for Marine Ecosystems and Human Health - Siregar, Rahmah Juliani; Mohamed , Rasidah Binti; Bagaskorowati, Riana (PT Inovasi Pratama Internasional, 2024)
This study aims to assess the level of microplastic contamination in the coastal waters of Southeast Asia and evaluate its impact on marine ecosystems and human health. Data were collected from various coastal locations in Southeast Asia, including Indonesia, Malaysia, Thailand, and the Philippines, using standard water and sediment sampling methods. Laboratory analysis was conducted to identify and measure microplastic concentrations. The results indicate that all surveyed locations were contaminated with microplastics at varying concentrations. Microplastics were found in significant amounts in surface water, sediments, and marine organisms such as fish and shellfish. The study also explores the potential impacts of microplastics on marine ecosystems, including disruptions to the food chain and the potential for bioaccumulation of harmful substances in marine organisms. Additionally, the potential health risks for humans consuming seafood contaminated with microplastics were evaluated. These findings highlight a serious threat to both marine ecosystems and human health in Southeast Asia. The study underscores the urgent need for actions to reduce the use of single-use plastics and improve plastic waste management to protect marine ecosystems and public health. Furthermore, it recommends increasing public awareness and implementing stricter policies related to plastic waste management to reduce microplastic contamination in coastal environments.